Knowledge Management strategies and processes in Agile Software Development: a systematic literature review - and Ouriques, Raquel Andrade Barros; Wnuk, Krzysztof; Gorschek, Tony; Svensson, Richard Berntsson (CoRR, 2018)
Knowledge-intensive companies that adopt Agile Software Development (ASD) relay on efficient implementation of Knowledge Management (KM) strategies to promotes different Knowledge Processes (KPs) to gain competitive advantage. This study aims to